The tensions between healthcare providers and patient and family advisory committees (PFACs): A comparative health system analysis between England and Ontario - Umair Majid (The Beryl Institute, 2021)
There has been a proliferation of patient engagement (PE) in healthcare activities. However, the concept of "engagement" has existed for decades; the first Patient and Family Advisory Committees (PFACs) in North America were formed in the 1970s. These committees are an important mechanism for involving patients and family and have proliferated across the healthcare sector. However, it is unclear how or why PFACs became the predominant mechanism for PE. The objective of this comparative analysis is to review the historical context and legislative imperatives that have contributed to the proliferation of PFACs in Ontario, Canada and England, United Kingdom. Experience Framework This article is associated with the Patient, Family & Community Engagement lens of The Beryl Institute Experience Framework (https://www.theberylinstitute.org/ExperienceFramework). <a href="https://www.theberylinstitute.org/page/PXSEARCH#resource-list-all/?view_28_page=1&view_28_filters=%5B%7B%22field%22%3A%22field_38%22%2C%22operator%22%3A%22in%22%2C%22value%22%3A%5B%22PXJ%20Article%22%5D%7D%2C%7B%22field%22%3A%22field_20%22%2C%22operator%22%3A%22is%22%2C%22value%22%3A%5B%22%22%5D%7D%2C%7B%22field%22%3A%22field_40%22%2C%22operator%22%3A%22is%22%2C%22value%22%3A%5B%22%22%2C%22Patient%2C%20Family%20%26%20Community%20Engagement%22%5D%7D%2C%7B%22field%22%3A%22field_41%22%2C%22operator%22%3A%22is%22%2C%22value%22%3A%5B%22%22%5D%7D%5D">Access other PXJ articles related to this lens. Access other resources related to this lens.